Answer:
Relationship between compound interest and exponential growth
C.I = [tex]P[(1 + \frac{R}{100})^{n} - 1][/tex]
where, P =Principal
R =Rate of interest, n= Duration i.e time interval for which money has been taken, C.I =Compound Interest
Exponential growth = A [tex](1+\frac{K}{100})^s[/tex]
Where , A=Initial value of population, K= Rate at which population is declining in percentage, s=total time between starting population and final population
Now , If you compare between Exponential growth and compound interest
P→(Replaced by)→A,
R→(Replaced by)→K,
n→(Replaced by)→s,
As C.I is calculated for money, and Exponential word is used for both money as well as increase in population.
So, just replacing keeping the meaning same
C.I = [tex]P[(1 + \frac{R}{100})^{n}][/tex] - P
→Compound Interest = Exponential growth - Initial Value(either money or any population considered)